UPAYA MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DENGAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY SISWA KELAS VII MTs SMQ MERANGIN - Rodianti Fitri Nengsih (LP3M | STKIP YPM Bangko, 2022)
This study aims to describe the application of the Two Stay Two Stray type of cooperative learning model to improve students' understanding of mathematical concepts in class VII A MTs SMQ Titian Teras. This research is a classroom action research (CAR), the subjects of this research are students of class VII A MTs SMQ Titian Teras totaling 31 people. The data collection instruments were activity observation sheets and mathematical concept understanding test sheets. The data analysis technique used statistical formulas and simple percentages. The research was conducted in III cycles. The results showed that students' understanding of mathematical concepts increased from 32.25% in the first cycle to 64.51% in the second cycle and increased to 93.54% in the third cycle. 70